KEANEKARAGAMAN BURUNG DI BERBAGAI TIPE HABITAT PADA EKOSISTEM RAWA GAMBUT YANG TERDEGRADASI DESA TANJUNG LEBAN AREA TRANSISI CAGAR BIOSFER GIAM SIAK KECIL BUKIT BATU, RIAU - Abdi Nazirwan; Haris Gunawan; Khairijon ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
High degradation of peat land in the village of Tanjung Leban, Bengkalis was suspected to affect the bird fauna in this region. This study aimed to determine species diversity and abundance of birds in the village of Tanjung Leban on three types of habitat : burned land, rubber, and oil palm plantations. The study was conducted from March to May 2014.The combination of transects with point count and mist nets were used in this study. The diversity of bird in study area was analyzed usingShannon index diversity. A total of 39 bird species were observed, they were grouped into 26 families. Columbidae and Pycnonotidae were the families that havethe highest abundance compared with other families. Shannon indexesfor the diversityof the birdwhich observed in threehabitats ranged from 2.275 to 2.699. The highest value of Shannon index was found in the rubber plantation habitat.